The solutions for construction of sea dike and sea embankments system as the sandy mud trap to support mangrove plants in the coastal zone of Hai Phong city, Vietnam - Vu, Doan Thai; Thai, Van Nam (Vietnam Journal of Marine Science and Technology, 2021)
Mangrove plants play a viral role in protecting the coast, retraining erosion. Especially in areas considered the variable wave conditions, complex dynamic conditions such as the coastal region of Hai Phong city. However, due to various reasons, the development/additional planting of mangrove forests in the coastal area of Hai Phong in some locations has not achieved the desired result. This study was conducted survey measurements of mangroves, terrain, and practical experience to assess the ecological impact of certain dynamic and sedimentary conditions on mangroves. Thereby proposing several solutions to build sea dykes/embankments suitable to Hai Phong conditions, strengthen sediment traps, and create favorable conditions for developing mangrove trees in this area.